Organic–inorganic hybrid cathode interlayer for efficient flexible inverted organic solar modules - Zhang, Lin; Yang, Fang; Deng, Wen; Guo, Xueliang; He, Yuxin; Zhou, Jixuan; Li, Haojie; Zhang, Yong; Zhou, Ke; Zhou, Conghua; Zou, Yingping; Yang, Junliang; et al. (Applied physics letters, 2023)
Organic solar cells (OSC) have great potential for flexible and wearable electronics due to their significant energy supply. However, the brittleness of inorganic electron transport layers (ETL) and their large-area production make it difficult to use them in flexible inverted OSCs. Herein, an organic–inorganic hybrid cathode interlayer of incorporating poly(4-vinylphenol) (P4VP) into the ZnO precursor solution was developed. The addition of P4VP improves the conductibility of ETL and facilitates the favorable vertical component distribution of active layer on the ZnO:P4VP substrate. Thus, the blade-coated OSC based on ZnO:P4VP performs better than the ZnO-based OSC in terms of photovoltaic performance and thickness insensitivity. The P4VP acts as an adhesive in ZnO grain boundaries and eliminates cracks in the bent ETL, leading to a significantly improved mechanical flexibility. Consequently, the ZnO:P4VP-based large-area flexible OSC achieves a power conversion efficiency of 14.05% and retains 80% of its initial efficiency after 1000 bending cycles, which is much better than that based on pristine ZnO (12.26%, 44%). Furthermore, flexible inverted organic solar modules were fabricated and achieved a considerable efficiency of 12.01%. These findings provide a general approach for using inorganic materials in flexible and wearable electronics.